Roma Hukukunda Hısımlık - (:unkn) unknown (My University, 2015)
Roma hukukunda doğumla ya da bazı hukukî ilişkiler sonucunda bir Roma vatandaşının, belli kişilerle arasında hısımlık kurulduğu ka- bul edilirdi. Roma hukuk dönemlerine göre hısımlık farklı esaslar üzeri- ne kurulmuştur. Romanın eski ve klasik hukuk döneminde geçerli olan hısımlık hâkimiyet esasına dayanan hısımlık (agnatio) idi. Ius civilede, modern hukuklardan farklı olarak kan hısımlığı esas alınmamıştır. Ius civile, aynı aile reisinin hâkimiyeti altında olanlar arasında doğan bağı hısımlık olarak görmektedir. Bu çeşit hısımlığın tanınmasının pek çok sakıncalar doğurması sebebiyle praetorların faaliyetleri kapsamında kan hısımlığının hukuken tanınması sağlanmıştır. Ius gentiumda kabul edilen kan hısımlığı (cognatio), zamanla ius civile tarafından da benim- senmeye başlamıştır. Iustinianus döneminde ise cognatio tek hısımlık biçimi olarak kabul edilmiştir.

In Roman law, it was accepted that a kinship was established between a Roman citizen and certain people by birth or as a result of some legal relationships. According to the Roman law periods, kinship was based on different principles. The kinship that was valid in Rome s early and classical law periods, was the kinship based on paternal po- wer (agnatio). In ius civile, in contrast to modern laws, blood kinship was not taken as a basis. Ius civile construes the relationship between persons who are under the paternal power (patria potestas) of the same pater familias as kinship. As the recognition of this kind of kinship gave rise to various drawbacks, it was provided that the blood kinship is legally recognized within the framework of the praetors activities. The blood kinship (cognatio) that was accepted by ius gentium, eventually started getting adopted by ius civile as well. In the time of Iustinianus, cognatio was accepted as the only form of kinship.
Relationship in Roman law
Keywords: Hukuk